A wavelet-based busbar differential protection - Silva, Kleber Melo e (2017)
This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication. Citation information: DOI 10.1109/TPWRD.2017.2764058, IEEE Transactions on Power Delivery.